A novel UPLC-MS/MS method identifies organ-specific dipeptide profiles - Heidenreich, Elena; Pfeffer, Tilman; Kracke, Tamara; Mechtel, Nils; Nawroth, Peter Paul; Hoffmann, Georg F.; Schmitt, Claus P.; Hell, Rüdiger; Poschet, Gernot; Peters, Verena (International journal of molecular sciences, 2021)
Background: Amino acids have a central role in cell metabolism, and intracellular changes contribute to the pathogenesis of various diseases, while the role and specific organ distribution of dipeptides is largely unknown. Method: We established a sensitive, rapid and reliable UPLC-MS/MS method for quantification of 36 dipeptides. Dipeptide patterns were analyzed in brown and white adipose tissues, brain, eye, heart, kidney, liver, lung, muscle, sciatic nerve, pancreas, spleen and thymus, serum and urine of C57BL/6N wildtype mice and related to the corresponding amino acid profiles. Results: A total of 30 out of the 36 investigated dipeptides were detected with organ-specific distribution patterns. Carnosine and anserine were most abundant in all organs, with the highest concentrations in muscles. In liver, Asp-Gln and Ala-Gln concentrations were high, in the spleen and thymus, Glu-Ser and Gly-Asp. In serum, dipeptide concentrations were several magnitudes lower than in organ tissues. In all organs, dipeptides with C-terminal proline (Gly-Pro and Leu-Pro) were present at higher concentrations than dipeptides with N-terminal proline (Pro-Gly and Pro-Leu). Organ-specific amino acid profiles were related to the dipeptide profile with several amino acid concentrations being related to the isomeric form of the dipeptides. Aspartate, histidine, proline and serine tissue concentrations correlated with dipeptide concentrations, when the amino acids were present at the C- but not at the N-terminus. Conclusion: Our multi-dipeptide quantification approach demonstrates organ-specific dipeptide distribution. This method allows us to understand more about the dipeptide metabolism in disease or in healthy state.